2011
DOI: 10.1007/s00024-011-0357-4
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Local Observations into the One Dimensional Fog Model PAFOG

Abstract: The numerical prediction of fog requires a very high vertical resolution of the atmosphere. Owing to a prohibitive computational effort of high resolution three dimensional models, operational fog forecast is usually done by means of one dimensional fog models. An important condition for a successful fog forecast with one dimensional models consists of the proper integration of observational data into the numerical simulations. The goal of the present study is to introduce new methods for the consideration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Their results also showed that PAFOG had ability to simulate stratiform clouds, where large‐scale subsidence played a critical role in suppressing the vertical growth and density rates of cloud. PAFOG is also widely used around the world (i.e., Kim, Yum, Hong, & Song, 2020; Kim, Yum, & Kim, 2020; Shi et al., 2012; Thoma et al., 2012). Thoma et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their results also showed that PAFOG had ability to simulate stratiform clouds, where large‐scale subsidence played a critical role in suppressing the vertical growth and density rates of cloud. PAFOG is also widely used around the world (i.e., Kim, Yum, Hong, & Song, 2020; Kim, Yum, & Kim, 2020; Shi et al., 2012; Thoma et al., 2012). Thoma et al.…”
Section: Introductionmentioning
confidence: 99%
“…Their results also showed that PAFOG had ability to simulate stratiform clouds, where large-scale subsidence played a critical role in suppressing the vertical growth and density rates of cloud. PAFOG is also widely used around the world (i.e., Kim, Yum, Hong, & Song, 2020;Shi et al, 2012;Thoma et al, 2012). Thoma et al (2012) suggested that PAFOG with a nudging scheme and application of observed visibility represented a distinct improvement over previous model versions, for forecasts of fog onset and dissipation times.…”
mentioning
confidence: 99%
See 1 more Smart Citation